Online Instructors’ Use of Scaffolding Strategies to Promote Interactions: A Scale Development Study - Moon-Heum Cho (Athabasca University Press, 2016)
A great deal of research has documented that interactions among students or between students and instructors are key to student success in an online learning setting. However, very little research has been statistically and systematically conducted to examine online instructors’ conscious and effortful use of scaffolding strategies to promote interactions in online courses. The purpose of this research was to develop a scale assessing online instructors’ use of scaffolding strategies to promote interactions. We employed a scale development method for the study. Exploratory factor analysis revealed one factor structure associated with instructors’ use of scaffolding strategies to promote interactions in online settings. Confirmatory factor analysis conducted with a different group of online students indicated that the one-factor model fits the data well. In addition, significant correlations with social presence and classroom learning community scales further demonstrated convergent validity. The new scale of online instructors’ use of scaffolding strategies to promote interactions demonstrated psychometrically sound validity and reliability.